PROCESS OF ECHELON II AUCTION IN ACEH GOVERNMENT IN 2017 - Muhammad Ikram Irvanda (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
The process of auction position in the Aceh Government environment is done through the process of fit and proper test in realizing transparency and accountability but in the implementation it gets many highlights from many parties hence the magnitude of a pubic hope and the warm political situation in Aceh because of the newly-appointed new Governor, this open selection is done based on Law No. 5 of 2014 concerning civil apparatus of the State which is then governed more specifically in the regulation of the Minister for State apparatus empowerment and bureaucracy reform No. 13 of 2014 on procedures of filling high leadership position in Government agency environment. A position auction in Aceh Government is done to fill vacating positions. This research aims to determine the process of implementing open selection of primary high-leadership officials in the Aceh Government environment and to know what are the supporting and inhibiting factors in implementing the open selection of management officials In the Aceh Government environment. The data needed in this study were derived from research results in the field and literature. The Data needed in this study were derived from the research results in the field. Research in the field is done by qualitative methods through interviews with informant and also from documents from the relevant office. Research in the field is conducted through interviews with informant and also from the important documents of the relevant service office. The results showed that: /one/ The selection process open the primary high-leadership office in the Aceh Government environment as a whole has run well even though there is still a shortage in its implementation. /two/ Supporting factor implementation of open selection process of primary high leadership office in Aceh Government because of the support from internal and external parties involved therein. /three/ The inhibitory factor affecting the implementation of the auction of the position in the Aceh Government environment is caused by several things namely budget, number of positions, and the length of time required for this implementation. The open selection process is expected to go better than before so that it can increase transparency in the selection process that will last in the future. In order for the future support of the various parties involved more escalating and the ensuing inhibitory can be improved to improve the open selection process later.Keywords: Process, Open Selection, Aceh Government.